2006
DOI: 10.1002/jcp.20730
|View full text |Cite
|
Sign up to set email alerts
|

Snail controls differentiation of hepatocytes by repressing HNF4α expression

Abstract: Epithelial-to-mesenchymal transition (EMT) is a coordinated process, occurring both during morphogenesis and tumor progression, that allows epithelial cells to dissociate from initial contacts and migrate to secondary sites. The transcriptional repressors of the Snail family induce EMT in different epithelial cell lines and their expression is strictly correlated with EMT during the development and progression of carcinomas. We have previously shown that EMT in hepatocytes correlates with the downregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 54 publications
(81 reference statements)
8
87
0
Order By: Relevance
“…As shown in Figure 3c, Snail overexpression caused a significant downregulation of endogenous miR-200c and -34a. Notably, TGF-b treatment, that triggers EMT and Snail expression in hepatocytes, 5,12 caused a transcriptional downregulation of these miRs in RLSCdH (Figure 3c). …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As shown in Figure 3c, Snail overexpression caused a significant downregulation of endogenous miR-200c and -34a. Notably, TGF-b treatment, that triggers EMT and Snail expression in hepatocytes, 5,12 caused a transcriptional downregulation of these miRs in RLSCdH (Figure 3c). …”
Section: Resultsmentioning
confidence: 98%
“…pWZL RLSCdH and pWZLSnail RLSCdH cells were generated by stable transfection by Lipofectamine 2000 (Invitrogen, San Diego, CA, USA), respectively, with empty or Snail carrying pWZL-bast vectors, as described previously. 5 Cells were selected in 5 mg/ml blasticidin for a week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, RLSCs and hepatocytes derived from their differentiation (RLSCdH) permitted to identify a simple cross-regulatory circuitry between HNF4 (master regulator of hepatocyte differentiation and MET inducer) and Snail (master regulator of the EMT), whose expression is mutually exclusive due to their direct reciprocal transcriptional repression (Cicchini et al, 2006;Santangelo et al, 2011). In particular, Cicchini and co-workers showed that Snail represses the HNF4 transcription through the direct binding to its promoter (Cicchini et al, 2006) and that Snail over-expression is sufficient i) to induce EMT in hepatocytes with change of morphology, down-regulation of several epithelial adhesion molecules, reduction of proliferation and induction of matrix metalloproteinase 2 expression and, ii) most relevantly, to directly repress the transcription of the HNF4α gene.…”
Section: Molecular Mechanisms Controlling Liver Stem Cell Fatementioning
confidence: 99%
“…In particular, Cicchini and co-workers showed that Snail represses the HNF4 transcription through the direct binding to its promoter (Cicchini et al, 2006) and that Snail over-expression is sufficient i) to induce EMT in hepatocytes with change of morphology, down-regulation of several epithelial adhesion molecules, reduction of proliferation and induction of matrix metalloproteinase 2 expression and, ii) most relevantly, to directly repress the transcription of the HNF4α gene. These findings demonstrated that Snail is at the crossroads of the regulation of EMT in hepatocytes by a dual control of epithelial morphogenesis and differentiation.…”
Section: Molecular Mechanisms Controlling Liver Stem Cell Fatementioning
confidence: 99%